Long Non-coding RNA JHDM1D-AS1 Interacts with DHX15 Protein to Enhance Non-Small-Cell Lung Cancer Growth and Metastasis - Guodong Yao; Kexin Chen; Yu Qin; Yangyang Niu; Xuefang Zhang; Shidong Xu; Chi Zhang; Meiyan Feng; Kuan Wang (Elsevier, 2019)
JHDM1D antisense 1 (JHDM1D-AS1), a long non-coding RNA (lncRNA), has been shown to promote pancreatic cancer growth by inducing an angiogenic response. However, its biological and clinical significance in non-small-cell lung cancer (NSCLC) is still unclear. In this study, we examined the expression and prognostic significance of JHDM1D-AS1 in NSCLC. The effects of JHDM1D-AS1 knockdown or overexpression on NSCLC growth and metastasis were investigated. We show that JHDM1D-AS1 is upregulated in NSCLC relative to adjacent normal lung tissues. High JHDM1D-AS1 expression is significantly correlated with advanced tumor, node, and metastasis (TNM) stage and lymph node metastasis. JHDM1D-AS1 expression serves as an independent prognostic factor for overall survival of patients with NSCLC. Functionally, JHDM1D-AS1 knockdown inhibits NSCLC cell aggressiveness both in vitro and in vivo, which is rescued by ectopic expression of JHDM1D-AS1. JHDM1D-AS1 binding stabilizes DHX15 protein in NSCLC cells. DHX15 overexpression enhances NSCLC cell proliferation and invasion, whereas knockdown of DHX15 exerts opposite effects. JHDM1D-AS1-mediated aggressive phenotype is impaired when DHX15 is silenced. Ectopic expression of DHX15 restores the defects in proliferation and invasion of JHDM1D-AS1-depleted NSCLC cells. Collectively, the interaction between JHDM1D-AS1 and DHX15 accounts for NSCLC growth and metastasis. This work provides potential additional therapeutic targets for treatment of NSCLC. Keywords: DHX15, lncRNA, lung cancer, metastasis, stabilization